Answer:
I think 30
Step-by-step explanation:
Answer:
-x¹⁴ / 5040
-½ < x < ½
Step-by-step explanation:
f(x) = e^(-x²)
The Taylor series for eˣ centered at 0 is:
eˣ = ∑ (1/n!) xⁿ
Substitute -x²:
e^(-x²) = ∑ (1/n!) (-x²)ⁿ
e^(-x²) = ∑ (1/n!) (-1)ⁿ x²ⁿ
The 14th degree term occurs at n=7.
(1/7!) (-1)⁷ x¹⁴
-x¹⁴ / 5040
ln(1 + x) = ∑ₙ₌₁°° (-1)ⁿ⁺¹ xⁿ / n
If we substitute 4x²:
ln(1 + 4x²) = ∑ₙ₌₁°° (-1)ⁿ⁺¹ (4x²)ⁿ / n
Using ratio test:
lim(n→∞)│aₙ₊₁ / aₙ│< 1
lim(n→∞)│[(-1)ⁿ⁺² (4x²)ⁿ⁺¹ / (n+1)] / [(-1)ⁿ⁺¹ (4x²)ⁿ / n]│< 1
lim(n→∞)│-1 (4x²) n / (n+1)│< 1
4x² < 1
x² < ¼
-½ < x < ½
Answer:
7.5
Step-by-step explanation:
(15/5)-0.4-0.4-0.4-0.4-0.4-0.4-0.4-0.2=0
Step-by-step explanation:
The ratio of the two shorter legs of the top triangle is
![\dfrac{5}{4} = 1.25](https://tex.z-dn.net/?f=%5Cdfrac%7B5%7D%7B4%7D%20%3D%201.25)
The bottom triangle has the following ratio:
![\dfrac{7.5}{6} = 1.25](https://tex.z-dn.net/?f=%5Cdfrac%7B7.5%7D%7B6%7D%20%3D%201.25)
Since their ratios are the same, this means that the two triangles are similar.
We need to expand the square binomial and then multiply:
<span>3x(x + 3)^2
= 3x(x + 3)</span>(x + 3<span>)
= 3x(x^2 + 6x + 9)
= 3x^3 + 18x^2 + 27x</span>